An analysis research of the stiffness characteristics of hospital building materials - Chen Yunyu (Fracture and Structural Integrity)
This paper primarily aims to introduce different stiffness ratio requirements for hospital buildings of various structural styles, to achieve a new standard. The requirements of each stiffness ratio are analyzed, according to the specification formulas and illustrations. And whether the structural deformation situation complies with the code requirement or dissatisfies the specification requests can be intuitively reflected through the application of the chart form, respectively. The corresponding measures complying with the code requirement and the matters needing attention in the schematic design phase are proposed. The comparison analysis for the lateral rigidity and lateral stiffness ratios is performed by applying different methods for the project cases of shear wall, frame tube and partial frame shear wall structures. The proposed computing method may better reflect the stiffness characteristics of the component’s cross-section, with regard to vertical layer, storey height and materials, as well as the actual situation of the turning constraint on both ends. The result thus determined can better reflect the real lateral rigidity of the construction, which is available as a benchmark for engineers designing hospital building structures.